SUMO Chains Rule on Chromatin Occupancy - Keiten-Schmitz, Jan; Schunck, Kathrin; Müller, Stefan (Frontiers in Cell and Developmental Biology, 2020)
The dynamic and reversible post-translational modification of proteins and protein complexes with the ubiquitin-related SUMO modifier regulates a wide variety of nuclear functions, such as transcription, replication and DNA repair. SUMO can be attached as a monomer to its targets, but can also form polymeric SUMO chains. While monoSUMOylation is generally involved in the assembly of protein complexes, multi- or polySUMOylation may have very different consequences. The evolutionary conserved paradigmatic signaling process initiated by multi- or polySUMOylation is the SUMO-targeted Ubiquitin ligase (StUbL) pathway, where the presence of multiple SUMO moieties primes ubiquitylation by the mammalian E3 ubiquitin ligases RNF4 or RNF111, or the yeast Slx5/8 heterodimer. The mammalian SUMO chain-specific isopeptidases SENP6 or SENP7, or yeast Ulp2, counterbalance chain formation thereby limiting StUbL activity. Many facets of SUMO chain signaling are still incompletely understood, mainly because only a limited number of polySUMOylated substrates have been identified. Here we summarize recent work that revealed a highly interconnected network of candidate polySUMO modified proteins functioning in DNA damage response and chromatin organization. Based on these datasets and published work on distinct polySUMO-regulated processes we discuss overarching concepts in SUMO chain function. We propose an evolutionary conserved role of polySUMOylation in orchestrating chromatin dynamics and genome stability networks by balancing chromatin-residency of protein complexes. This concept will be exemplified in processes, such as centromere/kinetochore organization, sister chromatid cohesion, DNA repair and replication.